Deubiquitinase OTUD1 Resolves Stalled Translation on polyA and Rare Codon Rich mRNAs - Snaurova, Renata; Vdovin, Alexander; Durech, Michal; Nezval, Jakub; Zihala, David; Jelinek, Tomas; Hajek, Roman; Simicek, Michal (Molecular and cellular biology, 2022)
OTUD1 is a deubiquitinating enzyme involved in many cellular processes including cancer and innate, immune signaling pathways. Here, we perform a proximity labeling-based interactome study that identifies OTUD1 largely present in the translation and RNA metabolism protein complexes. Biochemical analysis validates OTUD1 association with ribosome subunits, elongation factors and the E3 ubiquitin ligase ZNF598 but not with the translation initiation machinery. OTUD1 catalytic activity suppresses polyA triggered ribosome stalling through inhibition of ZNF598-mediated RPS10 ubiquitination and stimulates formation of polysomes. Finally, analysis of gene expression suggests that OTUD1 regulates the stability of rare codon rich mRNAs by antagonizing ZNF598.
Keywords: ribosome stalling; Deubiquitinating Enzymes; deubikvitinasy; kodon; translation; RNA, Messenger; Carrier Proteins; proteosyntéza; Poly A; poly A; Codon; Protein Biosynthesis; ubiquitination; messenger RNA; Ubiquitination; transportní proteiny; ubikvitinace